2013
DOI: 10.1073/pnas.1319113110
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of protein networks from an atlas of maize seed proteotypes

Abstract: A comprehensive knowledge of proteomic states is essential for understanding biological systems. Using mass spectrometry, we mapped an atlas of developing maize seed proteotypes comprising 14,165 proteins and 18,405 phosphopeptides (from 4,511 proteins), quantified across eight tissues. We found that many of the most abundant proteins are not associated with detectable levels of their mRNAs, and we provide evidence for three potential explanations: transport of proteins between tissues; diurnal, outof-phase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
163
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(180 citation statements)
references
References 50 publications
14
163
0
Order By: Relevance
“…This major effect on PPDK level confirms that pdk2-DsEx4 is a loss-of-function allele. The result further indicates that pdk1 conditions a minor portion of the endosperm enzyme, consistent with proteomic data showing PPDK1 to be 5% of the total (22) and enzyme activity data that follows. Loss of pdk1 function had no obvious effect on endosperm PPDK level, consistent with each form's abundance indicated from proteomic analysis.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This major effect on PPDK level confirms that pdk2-DsEx4 is a loss-of-function allele. The result further indicates that pdk1 conditions a minor portion of the endosperm enzyme, consistent with proteomic data showing PPDK1 to be 5% of the total (22) and enzyme activity data that follows. Loss of pdk1 function had no obvious effect on endosperm PPDK level, consistent with each form's abundance indicated from proteomic analysis.…”
Section: Resultssupporting
confidence: 88%
“…This genetic analysis confirms proteomics data (22,32) showing that the great majority of PPDK is specified by pdk2 in endosperm and pdk1 in leaf. The pdk1 and pdk2 products in endosperm are redundant with respect to maintenance of vitreous endosperm character.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, we explored the temporal relationships of the expression of each transcript and its encoded protein in Agave. When looking at relationships for a single time point, we observed non-linear relationships with weak correlations (average Pearson's correlation between log-transformed abundances was r = 0.48), which is consistent with results of previous studies 44 . The temporal dynamics between the expression of transcripts and their encoded proteins could explain this variation, which results from various rates of biosynthesis and degradation and subsequent post-transcriptional or -translational modifications.…”
Section: Detection Of Candidate Regulators Of Reprogrammed Metabolismsupporting
confidence: 91%
“…Recent studies with maize SBEIIb, the major isoform of SBEII in the starch-storing endosperm, have shown that the enzyme can be phosphorylated at three Ser sites by two plastidial Ca 21 -dependent protein kinase (CDPK) activities (14,70). Two of the phosphorylation sites (Ser 286 and Ser 297 ) are highly conserved among the SBEII class (see Fig.…”
Section: Regulation Of Sbes By Protein Phosphorylationmentioning
confidence: 99%